Differences in depression severity and frequency of relapses in opiate addicts treated with methadone or opiate blocker after detoxification - Jovanović Tatjana; Lazarević Dušan; Nikolić Gordana (Vojnosanitetski Pregled)
Background/Aim. Relapse of opiate dependence is a common occurrence after detoxification and introduction of opiate addicts in abstinence from opiates. Clinical evaluation showed that over 90% of opiate addicts exhibit depressive manifestations during detoxification, or develop post-detoxification depression. The aim of this study was to determine differences in the frequency of relapses, severity and course of depression during a of 6-month period, and previous patterns of use of opioids in the two groups of opiate addicts treated by two different therapeutic modalities. Methods. The results of the two groups of opiate addicts were compared: the patients on substitution methadone treatment (M) and the patients treated with opiate blocker naltrexone (B). In all the patients, clinical and instrumental evaluations confirmed depressive syndrome. Opioid relapses were diagnosed by the panel test for rapid detection of metabolites of opiates in urine. Then they were brought in connection with scores of depression and addiction variables. The Hamilton Depression Scale (HAMD) and Zunge Depression Scale were the applied instruments for measuring the level of depression. All the subjects completed a questionnaire Pompidou (short version). Psychological measurements were carried out during a 6-month follow-up on three occasions. The presence of opiate metabolites in urine was controlled every two weeks. Results. Both groups of patients (M and B) had high scores on HAMD during the study. The group on methadone had a strong depression in all three measurements. There was a drop in the level of depression in both experimental groups over time, which was accompanied by a decrease in the incidence of recurrence. In both tested groups the frequency of relapses was positively correlated with earlier addiction variables - intravenous application of opioids, the experience of overdose, the absence of immunization against hepatitis C and hepatitis C virus carriers. Conclusion. The opioid relapse behavior is associated with a marked depression in post-detoxification period. The tested group M had a more expressed depression which is consistent with the literature data. In both tested groups the frequency of relapses was positively correlated with individual addiction variables associated with latent suicidal behavior. Diagnosing and monitoring depression of opiate addicts as well as timely remediation of post-detoxification depression symtoms, could help in prevention of opiate relapse.